MODEL JARINGAN DISTRIBUSI AIR BERSIH DI KELURAHAN PONDOK CINA, KECAMATAN BEJI, KOTA DEPOK MENGGUNAKAN SOFTWARE EPANET 2.0 - Diyanti Diyanti; Fani Yayuk Supomo (Jurnal Infrastruktur, 2021)
Clean water is water that can be used for daily needs, where the quality must meet health requirements. The clean water distribution network is a water distribution network whose existence is functioned to fulfill the community's water needs in a city or as groundwater conservation. The simulation model for the clean water distribution network in Pondok Cina Subdistrict, Beji District, Depok City, West Java aims to obtain a simulation of the need for clean water in the next 20 years. This modeling is done with the help of epanet 2.0 software with population projection methods, namely arithmetic, geometric, and least square methods. The next stage is to predict the need for clean water by referring to the standards set by the West Java PPSAB and the Directorate General of Human Settlements of the Ministry of Public Works and Housing, and SNI 03-1733-2004 on procedures for planning housing environments in urban areas in the technical guidelines for technical design procedures in the drinking water sector, as well as SNI 7509: 2011 concerning procedures for engineering planning of distribution networks and service units for the drinking water supply system. The results of the modeling of clean water distribution networks using the projection method accepted by the geometric method, where the prediction of the population in 2039 is 14,924 people, so it takes an average daily water of 24,53 liters / second, maximum water 26, 98 liters / second, and peak water 36,80 liters / second. The hydraulic simulation results obtained a reservoir capacity of 360 m3, type of HDPE pipe with a diameter of 5 inch primary distribution pipe, 0,5 inch secondary pipe, and 8,20 meter pump head.